Togo : Poverty Reduction Strategy Paper (2009-11). (IMF Staff Country Reports; Country Report ;, 2010)
This paper focuses on Togo's Poverty Reduction Strategy. The Interim Poverty Reduction Strategy Paper adopted by the government in March 2008 has allowed Togo once again to benefit from international financial cooperation. With a view to improving political and economic governance, the government continued the ongoing process of national reconciliation and political reform, strengthening the rule of law and the security of persons and property, and implementation of institutional reforms. The government has introduced reforms designed to improve governance in nonperforming state enterprises and in the banking sector.